2019
DOI: 10.1136/bmjgh-2018-001114
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tests for Crimean-Congo haemorrhagic fever: a widespread tickborne disease

Abstract: Crimean-Congo haemorrhagic fever (CCHF) is a widespread tickborne disease that circulates in wild and domestic animal hosts, and causes severe and often fatal haemorrhagic fever in infected humans. Due to the lack of treatment options or vaccines, and a high fatality rate, CCHF virus (CCHFV) is considered a high-priority pathogen according to the WHO R&D Blueprint. Several commercial reverse transcriptase PCR (RT-PCR) and serological diagnostic assays for CCHFV are already available, including febrile agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 132 publications
(168 reference statements)
2
55
0
Order By: Relevance
“…Diagnostics developers had to purchase specimens without guarantee of the quality of the clinical characterisation (which is of particular importance for the Zika virus due to the high immunological cross-reactivity with dengue virus and other flaviviruses) 30. Efforts to validate diagnostic tests for the WHO R&D Blueprint pathogens CCHF and MERS-CoV have also been hampered by difficulties with sourcing of clinical specimens, as described elsewhere in this supplement 15 18…”
Section: Challenges To Diagnostic Preparednessmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostics developers had to purchase specimens without guarantee of the quality of the clinical characterisation (which is of particular importance for the Zika virus due to the high immunological cross-reactivity with dengue virus and other flaviviruses) 30. Efforts to validate diagnostic tests for the WHO R&D Blueprint pathogens CCHF and MERS-CoV have also been hampered by difficulties with sourcing of clinical specimens, as described elsewhere in this supplement 15 18…”
Section: Challenges To Diagnostic Preparednessmentioning
confidence: 99%
“…Linking diagnostics and vaccines in a common health programme would help to ensure that vaccines are delivered in a timely manner to the most at-risk populations. For pathogens with significant animal reservoirs, such as the Nipah and CCHF viruses, collection and integration of animal surveillance data may also be a necessary component of any outbreak preparedness strategy 15 17. A ‘One Health’ approach to surveillance that integrates human, animal and ecological health would provide earlier opportunities for outbreak detection and prevention; however, a number of challenges to implementing such an approach exist, including need for greater cross-sectoral communication, strengthening of laboratory networks, restructuring of existing systems, and development of shared databases, shortage of experienced personnel and limited availability of diagnostic tests suitable for animal use 37…”
Section: Challenges To Diagnostic Preparednessmentioning
confidence: 99%
See 1 more Smart Citation
“…The important laboratory tests used to diagnose the CCHF virus include the enzyme‐linked immunosorbent assay (ELISA), which detects IgM and IgG antibodies in the serum (Samudzi et al . 2012), RT‐PCR and qRT‐PCR for the detection of the viral genome, virus isolation by culture, and other serological diagnostic assays (Mazzola & Kelly‐Cirino 2019). Interestingly, Vanhomwegen et al .…”
Section: Crimean–congo Hemorrhagic Fever Virusmentioning
confidence: 99%
“…Turnaround time for each test is specified by the manufacturer; turnaround time per result can include additional time (days to weeks) for sample transport and processing at the reference lab. Several commercial assays for PCR and serology are available (online supplementary table S1 and S2),although the majority of international laboratories use inhouse assays, likely due to an investment in tests developed from regional CCHV strains.It has also been suggested that commercial tests may be too expensive, difficult to order or not available to international customers.The majority of the inhouse assays have a publication history, several with published data on diagnostic performance or external quality assessment 12 .…”
Section: Diagnosismentioning
confidence: 99%